SUBALTERN DALAM NOVEL PROMISE, LOVE AND LIFE KARYA NYI PENENGAH DEWANTI: KAJIAN POSTKOLONIAL GAYATRI SPIVAK - Prihatin, Yulianah; Mayasari, Diana (UNIB Press, 2021)
This research is motivated by the existence of colonial influences in the archipelago which are still imprinted on people's lives, to the literary works created. In the theory coined by Gayatri Spivak, it is known as subaltern, namely groups that are victims of marginalization and hegemony from groups in power and do not have access to voice. Based on this background, this study aims to describe various forms of impoverishment, violent behavior both physically and psychologically as well as in subaltern groups, employer hegemony and resistance from subalterns in the novel promise, love and live. The method used is descriptive qualitative with data collection through observation, documentation, instruments in the form of a check list table. The data analysis technique is by reviewing Gayatri Spivak's postcolonial theory in the markers of subalterns and their forms of resistance. The results of this study that the subalterns in the novel Promis, Love and Life are depicted from the character of Dewi who is never voiced and the resistance that is carried out is a tangible form that the subaltern cannot voice his opinion and is represented by certain groups with an attitude of submission to God, enthusiasm and writing skills are form of resistance that can be done. Dewanti as a form of resistance also describes the form of political ideology, so that in fact the subaltern has never been represented by its voice.